Association of Antiplatelet and Anticoagulant Treatment in Patients with Mechanical Prosthetic Heart Valves. Data from the Observational Multicentre PLECTRUM Study - Poli, Daniela; Antonucci, Emilia; Pengo, Vittorio; Bucherini, Eugenio; Lodigiani, Corrado; Barcellona, Doris; Palareti, Gualtiero; Testa, Sophie (Cardiology and Cardiovascular Medicine, 2021)
Background: Patients with a mechanical prosthetic heart valve (MHV) need vitamin K antagonist (VKA) treatment, due to the high thrombotic risk. Guidelines disagree in relation to the need of lowdose aspirin associated treatment (VKA+apl). In the dataset of PLECTRUM study, we evaluate the number and characteristics of patients treated with VKA+apl, their bleeding and thrombotic risk. Methods: Observational retrospective multicenter study among Centers affiliated to the Italian Federation of Anticoagulation Clinics (FCSA) on patients with MHV. Results: 237/2051 (11.5%) enrolled patients were treated with VKA + apl. These patients were older than patients on single VKA treatment, more frequently males, have a higher rate of cardiovascular risk factors, higher prevalence of coronary artery disease, peripheral arterial obstructive disease, Stroke/transient ischemic attack (TIA), heart failure, and atrial fibrillation. Instead, no difference was found between patients on VKA and patients on VKA + apl in relation to the site of valvular implantation (aortic, mitralic or mitro-aortic) and to the intensity of anticoagulation. The rate of major bleedings, of Stroke/TIA and of death were higher in patients on VKA +apl with respect to patients treated with VKA. Conclusions: Patients with MHV followed in Italian Anticoagulation Clinics usually receive single VKA treatment. VKA +apl is limited to patients with concomitant arterial disease or at high cardiovascular risk. VKA +apl did not reduce the stroke risk of these patients and is associated with a trend to an increased bleeding risk.